Electrospinning of Chitosan–Halloysite Nanotube Biohybrid Mats for Clobetasol Propionate Delivery - Natallia V. Dubashynskaya; Valentina A. Petrova; Igor V. Kudryavtsev; Andrey S. Trulioff; Artem A. Rubinstein; Alexey S. Golovkin; Alexander I. Mishanin; Anton A. Murav’ev; Iosif V. Gofman; Daria N. Poshina; Yury A. Skorik (Technologies)
The application of electrospinning technologies for the preparation of mats based on mucoadhesive polysaccharides, such as chitosan (CS), is an attractive strategy for the development of biopolymeric delivery systems for topical corticosteroids. In this work, an electrospinning technique is described for the preparation of CS-based mats doped with halloysite nanotubes (HNTs) with modified release of clobetasol propionate (CP). The optimized composition of the electrospinning solution was determined: 2.4% solution of CS in 46% acetic acid with addition of PEO (10% of CS mass) and HNTs (5% of CS mass); CP was introduced as an ethanol solution at the rate of 2 mg CP per 1 g of the obtained nonwoven material. The process parameters (the electrospinning voltage of 50–65 kV, the rotation speed of the spinning electrode of 10 min−1, and the distance between the electrodes of 24 cm) were also optimized. The developed technology allowed us to obtain homogeneous nanofiber mats with excellent mechanical properties and biphasic drug release patterns (66% of CP released within 0.5 h and 88% of CP released within 6 h). The obtained nanofiber mats maintained the anti-inflammatory activity of corticosteroid at the level of free CP and showed no cytotoxicity.